Analisis Linguistik Kritis terhadap Kesalahan Berbahasa di Ruang Publik dan Implikasinya terhadap Literasi Masyarakat - Pratidina Trihuningsih; Liliana Muliastuti; Siti Ansoriyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Language errors in public spaces are still frequently found in various media, such as signboards, banners, billboards, and posters. This phenomenon not only indicates a deviation from standard Indonesian language rules but also has the potential to influence how people understand and use language. This study aims to describe the forms of language errors in public spaces, analyze them from a critical linguistic perspective, and identify their implications for public literacy. The method used is descriptive qualitative research with a critical linguistic analysis approach. Data in the form of examples of language use in public spaces are analyzed based on aspects of spelling, diction, and sentence structure, then interpreted in relation to the social practices and ideologies that underlie them. The results of the study indicate that the dominant language errors include spelling errors, inappropriate word choice, and the use of ineffective sentence structures. From a critical linguistic perspective, these errors are not only caused by a lack of mastery of language rules but are also influenced by social habits, the reproduction of deviant language practices, and the tendency to use foreign languages ​​to construct a certain image. These findings indicate that repeated exposure to language that does not conform to rules can affect the quality of public literacy. Therefore, it is necessary to strengthen critical literacy and increase language awareness so that society is able to use and evaluate language more appropriately and responsibly.